Culture & rhetoric - Strecker, Ivo A., 1940-; Tyler, Stephen A., 1932- (Studies in rhetoric and culture ;, 2009)
While some scholars have said that there is no such thing as culture and have urged to abandon the concept altogether, the contributors to this volume overcome this impasse by understanding cultures and their representations for what they ultimately are - rhetorical constructs. These senior, international scholars explore the complex and multifarious relationships between culture and rhetoric arguing that just as rhetoric is founded in culture, culture is founded in rhetoric. This intersection of rhetoric and culture constitutes the central theme of the first part of the book, while the second.